Data from: Sex-biased transcriptomic response of the reproductive axis to stress - Calisi, Rebecca M.; Austin, Suzanne H.; Lang, Andrew S.; MacManes, Matthew D. (Dryad, 2019)
Stress is a well-known cause of reproductive dysfunction in many species,
including birds, rodents, and humans, though males and females may respond
differently. A powerful way to investigate how stress affects re-
production is by examining its effects on a biological system essential
for regulating reproduction, the hy- pothalamic-pituitary-gonadal (HPG)
axis. Often this is done by observing how a stressor affects the amount of
glucocorticoids, such as cortisol or corticosterone, circulating in the
blood and their relationship with a handful of known HPG-producing
reproductive hormones, like testosterone and estradiol. Until now, we have
lacked a full understanding of how stress affects all genomic activity of
the HPG axis and how this might differ between the sexes. We leveraged a
highly replicated and sex-balanced experimental approach to test how male
and female rock doves (Columba livia) respond to stress at the level of
their transcriptome. Females exhibit increased genomic responsiveness to
stress at all levels of their HPG axis as compared to males, and these
responsive genes are mostly unique to females. Reasons for this may be due
to fluctuations in the female endocrine environment over the reproductive
cycle and/or their evolutionary history, including parental investment and
the potential for maternal effects. Direct links between genome to phenome
cause and effect cannot be ascertained at this stage; however, the data we
report provide a vital genomic foundation on which sex-specific
reproductive dysfunction and adaptation in the face of stress can be
further experimentally studied, as well as novel gene targets for genetic
intervention and therapy investigations.
RockDove.HPG.v1.1.0Transcriptome Assembly
Keywords: Columba livia